KAJIAN TEORITIS TENTANG KEMAMPUAN BANGSA DALAM MERESPON GLOBALISASI - Iqbal Anggia Yusuf (HASBUNA : Jurnal Pendidikan Islam, 2024)
The purpose of this study is to explore or reveal a set of concepts or regulations set by the state as principles or guidelines that are the handle, foothold, reference or backing in the life of the nation and state. The method used to collect data is a literature study, by collecting relevant data from books, dictionaries, journals, magazines, and so on without having to conduct a field review. This research found that these national norms and values are contained in the basic philosophy of the state, namely Pancasila, the 1945 Constitution, the Outlines of the State Direction (GBHN), Bhineka Tunggal Ika and the Unitary State of the Republic of Indonesia (NKRI). Globalization is essentially the idea of a certain party or country which is then offered to other parties or countries to be followed by a certain cause. This requires a period of time, so it is a process that continues to roll over time, time to time. One of the characteristics of the development of globalization is the rapid development of technology. The nation's response in facing globalization has been carried out by the government with several positive steps as contained in the GBHN which consists of strengthening the economic field, political field, religion field, education field and sociocultural field, so that it is expected to become the nation's strength in facing the pace of globalization that continues to develop widely in the midst of the life of the Indonesian people.